Effect of emotional victim images in prosocial advertising: The moderating role of helping mode. Issue 4 (14th May 2020) - Li, Dan; Atkinson, Lucy
Abstract : Charities and marketers routinely incorporate images of recipients, for example victims of a flood or famine, in their prosocial advertising; however, previous literature suggests mixed results regarding the effectiveness of relying on sad versus happy images of victims. Recently, due to reactance to excessively traumatic marketing campaigns, happy victim images have been found to be more effective in eliciting prosocial behaviors. To extend this line of research, an experiment found that consumers are more willing to help when viewing advertisements featuring happy children over sad children. Moreover, helping mode moderates the relationship between victim image and helping intentions. The effect of a happy victim image is attenuated when consumers are asked to buy cause‐related products rather than donate to charities. According to emotion regulation consumption theory, consumers mitigate the feeling of negative emotions by increasing their intention to buy cause‐related products. Practically, the findings provide guidance on integrating victim images in prosocial advertising.